The twelve prophets ; v. 2 - Craigie, Peter Campbell, 1938-1988 (Edinburgh, Scotland Saint Andrew, 1985)
Contents : v. 2 : Micah, Nahum, Habakkuk, Zephaniah, Haggai, Zechariah And Malachi. Includes bibliographical references.
Keywords: Bible. O.T. Minor prophets -- commentaries